2021
DOI: 10.5194/hess-2021-350
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Remotely sensed reservoir water storage dynamics (1984–2015) and the influence of climate variability and management at global scale

Abstract: Abstract. Many thousands of large dam reservoirs have been constructed worldwide during the last seventy years to increase reliable water supplies and support economic growth. Because reservoir storage measurements are generally not publicly available, so far there has been no global assessment of long-term dynamic changes in reservoir water volume. We overcame this by using optical (Landsat) and altimetry remote sensing to reconstruct monthly water storage for 6,743 reservoirs worldwide between 1984 and 2015.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…Various attempts have been made to infer reservoir operation signals from different types of data sources including optical and altimetry remote sensing (Peng et al, 2006;Eldardiry and Hossain, 2019;Hou et al, 2021;Du et al, 2022), reservoir purpose, simulated inflows and water withdrawals (Hanasaki et al, 2006;Voisin et al, 2013) or in-and outflows (Turner et al, 2021). To identify the time scales most affected by reservoir operation, White et al (2005) and Shiau and Huang (2014) used the wavelet transform on both observed in-and outflow time series and compared their wavelet power spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Various attempts have been made to infer reservoir operation signals from different types of data sources including optical and altimetry remote sensing (Peng et al, 2006;Eldardiry and Hossain, 2019;Hou et al, 2021;Du et al, 2022), reservoir purpose, simulated inflows and water withdrawals (Hanasaki et al, 2006;Voisin et al, 2013) or in-and outflows (Turner et al, 2021). To identify the time scales most affected by reservoir operation, White et al (2005) and Shiau and Huang (2014) used the wavelet transform on both observed in-and outflow time series and compared their wavelet power spectra.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in all regions, reservoirs increase the duration of extreme events by increasing the spatial connectedness (Brunner, 2021). Decreasing storage trends have also been linked to decreasing reservoir resilience in the southwestern regions and the Mississippi basin where reservoir storage has struggled to recover after recent droughts (Hou, van Dijk, Beck, Renzullo, & Wada, 2021). This is contrasted by Giuliani and Herman (2018), who found that large dams in California with limited storage fluctuations are more drought resilient than smaller dams.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have noted declining reservoir storage across the US over time. Nationally, reservoir storage has declined by at least 10% over the past thirty years (Adusumilli et al, 2019;Hou et al, 2021;Randle et al, 2021;Zhao & Gao, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations